Scales of Captivity : Racial Capitalism and the Latinx Child - Brady, Mary Pat, 1961- (Book collections on Project MUSE., 2022)
"Mary Pat Brady traces the figure of the captive and cast-off child over 150 years of Latinx/Chicanx literature as a critique of colonial modernity and the forms of confinement that underpin racialized citizenship."--